Kinetic modelling of the synthesis of sorbitol-branched polyester for the production of bio-based polyurethane - Chin, Sim Yee (2014)
A bio-based polyester polyol was synthesised through the esterification of azelaic acid and sorbitol catalysed by tin (II) oxide. The chemical equilibrium, reaction kinetics and parametric studies were carried out. Different reaction parameters were studied in order to determine the best reaction conditions. The best operating condition with reaction temperature of 433K, sorbitol to azelaic acid molar ratio of 4:1 and catalyst loading of 2wt%, yielded a conversion of 72%. The formation of sorbitol based branched polyester with its backbone incorporated with sorbitan and isosorbide was affirmed. The mathematical form of Eley Rideal (ER) model gave good agreement with the experimental data. The activation energy was found to be 47.62 kJ/mol.